ANALYSIS OF THE EFFECTIVENESS OF PUBLIC SERVICES AFTER SUB-DISTRICT EXPANSION IN THE WANIA DISTRICT, MIMIKA REGENCY - Samangun, Adelya; Bakar, Abu (APPS Publications, 2023)
This study aims to determine the effectiveness of public services in the Wania District. The research method used in this research is descriptive quantitative research method. The data used are qualitative and quantitative data collected using observation, interviews, and questionnaires. To measure the effectiveness of public services after the expansion of the Wania District, an effectiveness analysis tool was used. With development in accordance with the objectives of this study. The results of this study indicate that the effectiveness of public services after the expansion of the Wania District on the indicators of timeliness, certainty and simplicity of procedures, reasonable costs, information, and security has been effective.